Os indígenas e o texto teatral no Brasil: um breve itinerário - Dennys Silva-Reis; Wesley Alves Batista (Das Amazônias)
The study of indigenous issues has had a major impact on the Humanities, including the areas of Literary Studies and Performing Arts.Thus, this work highlights the presence of indigenous themes in theatrical texts produced in Brazil over time.Our goal is to offer a concise historiography of plays that address indigenous people as characters or list indigenous issues, whether cultural, social, political or artistic, as their subject.To this end, we have adopted a division into “theatrical periods”, namely: Jesuit Theater, Indianist Theater, Theater about indigenous people in the 20th and 21st centuries and Indigenous Theater, tobe able toexemplify sets of plays from different moments in Brazilian Literary History.Thus, we have mapped and listed an inventory of published dramaturgies that contemplate native peoples and by indigenous and non-indigenous authors.Hopefully,this text will be an encouraging milestone for new research on this subject with analyses of the plays mentioned here, as well as providing interest in the staging of such dramatic works.